Determinants of Dietary Adherence in Elderly with Hypertension - Sari, Ilma Widiya (LPPM UNIKAL, 2025)
Hypertension is most common in elderly people, for which a hypertension diet is an important strategy to control it. Dietary adherence in the elderly is related to various factors including other self-efficacy, motivation and family support. Elderly have low dietary adherence so it is necessary to identify the determining factors. This research aims to analyze the factors most influential in hypertension dietary adherence in the elderly. An analytical design using a cross-sectional method was applied in this study. The study population consisted of 75 elderly people with a history of hypertension. Bivariate analysis was performed using the chi-square test, while logistic regression was applied for multivariate analysis. The findings indicated significant associations between self-efficacy (p = 0,000), motivation (p = 0,001), and family support (p = 0,001) with adherence to a hypertension diet. The odds ratio value indicates that self-efficacy is the most significant factor affecting dietary adherence. The results of this study strengthen empirical evidence and current theory that self-efficacy has a major role compared to motivational and family support in influencing dietary adherence in elderly people with hypertension. Implications for nursing practice are the need for intervention approaches that target increasing self-efficacy through structured education to improve dietary adherence in the elderly with hypertension.